Utilization of crops residues as compost and biochar for improving soil physical properties and upland rice productivity - J Barus (Brawijaya University, 2016)
The abundance of crops waste in the agricultural field can be converted to organic fertilizer throughout the process of composting or pyrolysis to return back into the soil. The study aimed to elucidate the effect of compost and biochar application on the physical properties and productivity of upland rice at Village of Sukaraja Nuban, Batanghari Nuban Sub district, East Lampung Regency in 2015. The amendment treatments were A. control; B. 10 t rice husk biochar/ ha; C. 10 t maize cob biochar/ha; D. 10 t straw compost/ha; E. 10 t stover compost/ha, F. 10 t rice husk biochar/ha + 10 t straw compost/ha; F. 10 t maize cob biochar/ha + 10 t maize stover compost/ha. The treatments were arranged in randomized block design with four replicates. The plot size for each treatment was 10 x 20 m. After incubation for about one month, undisturbed soil samples were taken using copper ring at 10–20 cm depth for laboratory analyzes. Analyses of soil physical properties included bulk density, particle density, total porosity, drainage porosity, and soil water condition. Plant observations conducted at harvest were plant height, number of panicle, number of grain/panicle, and grain weight/plot. Results of the study showed that biochar and compost improved soil physical properties such as bulk density, total porosity, fast drainage pores, water content, and permeability of soil. The combination of rice husk biochar and straw compost gave better effect than single applications on rice production components (numbers of panicle and grains of rice), and gave the highest yield of 4.875 t/ha.